Cognitive changes in people with diabetes with lower extremity complications compared to people with diabetes without lower extremity complications: a systematic review and meta-analysis - Nimantha Karunathilaka; Christina Parker; Peter A. Lazzarini; Pamela Chen; Chloe Katsanos; Margaret MacAndrew; Kathleen Finlayson (BMC Endocrine Disorders)
Abstract Background Recent evidence suggests that diabetes-related lower-extremity complications (DRLECs) may be associated with cognitive changes in people with diabetes. However, existing literature has produced inconsistent findings, and no systematic reviews have been conducted to investigate whether DRLECs impact the cognition of people with diabetes. This systematic review evaluated existing studies that investigated cognition in people with diabetes with DRLECs and without DRLECs. Method Seven databases; MEDLINE, PubMed, CINAHL, EMBASE, Cochrane, PsycINFO and Web of Science were searched from inception until 22/8/2022 for studies that compared cognition in people with diabetes with and without DRLECs. Results were independently screened for eligibility and assessed for methodological quality by two authors, with key data extracted. Studies were eligible for meta-analysis if the studies reported similar cases, controls, and outcome measures. Results Thirteen studies were included in the review, with eleven of medium methodological quality, one of high quality, and one of low quality. Four studies found significant differences in cognition between those with and without DRLECs, four found significant associations between diabetes-related lower-extremity complications and cognition, and five found no differences or associations. One small meta-analysis of eligible studies found that there was no statistically significant difference in cognition in people without, compared to with, peripheral neuropathy (Mean difference = -0.49; 95%CI: -1.59–0.61; N = 3; n = 215). Leave-one-out sensitivity analyses further confirmed that there was no significant difference in cognition among people with and without peripheral neuropathy (p > 0.05). Conclusion DRLECs may be related to cognition in people with diabetes, however, existing evidence is unclear due to variability in used methodologies that may challenge concluding the findings. Future high-quality studies investigating cognition among people with and without DRLECs are needed.